How Do Expectations about the Macroeconomy Affect Personal Expectations and Behavior? - Roth, Christopher; Wohlfart, Johannes (The Review of Economics and Statistics, 2020)
Using a representative online panel from the United States, we examine how individuals' macroeconomic expectations causally affect their personal economic prospects and their behavior. To exogenously vary respondents' expectations, we provide them with different professional forecasts about the likelihood of a recession. Respondents update their macroeconomic outlook in response to the forecasts, extrapolate to expectations about their personal economic circumstances, and adjust their consumption plans and stock purchases. Extrapolation to expectations about personal unemployment is driven by individuals with higher exposure to macroeconomic risk, consistent with macroeconomic models of imperfect information in which people are inattentive but understand how the economy works.